The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ptr.5855
|View full text |Cite
|
Sign up to set email alerts
|

Neuro‐Protective Effects of Resveratrol on Carbon Monoxide‐Induced Toxicity in Male Rats

Abstract: Acute carbon monoxide (CO) poisoning causes neurotoxicity through induction of necrosis, apoptosis, lipid peroxidation and oxidative stress. Resveratrol (RES) is a natural polyphenolic phytoalexin that exhibits neuroprotective effects in ischemia/reperfusion due to its anti-apoptotic, anti-necrotic and strong anti-oxidant properties as well as its ability to activate pro-survival pathways. In this study, rats were exposed to CO 3000 ppm for 1 h. Immediately after poisoning and on the next four consecutive days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
0
14
1
1
Order By: Relevance
“…On the other hand, resveratrol (RSV; 3,5,4′-Trihydroxystilbene), a natural phytoalexin extracted from the root of veratrum grandiflorum, was widely found in a diversity of plants such as grape, peanut, hellebore and so on. Further, reports have shown that RSV had multiple pharmacological properties including antioxidant [ 17 ], anti-inflammation [ 18 ], anti-necrosis [ 19 ], anti-proliferation [ 20 ] and anti-cancer [ 21 ]. Moreover, accumulating evidence has indicated bone-protective effects of RSV.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, resveratrol (RSV; 3,5,4′-Trihydroxystilbene), a natural phytoalexin extracted from the root of veratrum grandiflorum, was widely found in a diversity of plants such as grape, peanut, hellebore and so on. Further, reports have shown that RSV had multiple pharmacological properties including antioxidant [ 17 ], anti-inflammation [ 18 ], anti-necrosis [ 19 ], anti-proliferation [ 20 ] and anti-cancer [ 21 ]. Moreover, accumulating evidence has indicated bone-protective effects of RSV.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) is a toxic gas produced by the incomplete combustion of fossil fuels (1,2). It is a cause of significant morbidity and mortality worldwide with no specific antidote.…”
Section: Introductionmentioning
confidence: 99%
“…Activated Akt influences a number of factors involved in apoptosis, either by transcription regulation or direct phosphorylation, yielding favorable effects against ischemia-induced apoptosis. Thus, chemicals capable of inducing Akt expression/activity may be used in the treatment of I/R injury (2,3235).…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance of the supernatant was measured at 532 nm, and the amount of MDA is expressed as nmol per gram of wet tissue. [5,25]…”
Section: Thiobarbituric Reactive Substances Assaymentioning
confidence: 99%
“…[4] Natural products are receiving growing attention from the research community due to their phytochemical, biological and pharmacological properties. [5] Umbelliprenin (UMB) is a 7-farnesyloxycoumarin found mainly in Genera Ferula, Peucedanum, Seseli, Magydaris and Ammi. UMB was isolated from the roots of Ferula szowitsiana DC, a plant with analgesic activity as recommended by the Iranian traditional medicine, [6] while it is believed to contribute to the analgesic action of F. szowitsiana.…”
Section: Introductionmentioning
confidence: 99%